PAŁAC W PODHORCACH W LATACH 1865 –1939. STAN BADAŃ I POSTULATY BADAWCZE - Paduch, Katarzyna (Saeculum Christianum. Pismo Historyczne, 2017)
The palace in Podhorce has been, and remains, the subject of many studies and articles, but not all aspects of the history of this residence have been studied. This paper presents the state of research on the history of the Podhorce palace in the years 1865-1939. Ownership of the palace by Princess Constance of Zamoyskich Sanguszko (1864-1946) and Stanislaw Eustachy Sanguszko (1842-1903) still awaits studying. For researchers of the mansion Podhorce history, the most difficult challenges are related to detailed examining of source documents presenting fortunes of the palace on a background of important historical events. In the years 1865-1939 breakthrough moments for the Podhorce mansion were: World War I, the war of 1920, the celebration of the 250th anniversary of the Battle of Vienna, the outbreak of World War II. However the administration and care of goods in Podhorce is the issue least studied.